Legal Certainty Guarantees for Children’s Identity Rights from Unregistered Marriages: A Comparative Study in Indonesia and Malaysia - Ahmad Muzaki; Hidayatun Ulfa; Muhajir (Yayasan Azhar Amanaa Yogyakarta, 2026)
Unregistered marriage constitutes a legal issue that potentially threatens legal certainty regarding children’s identity rights in both Indonesia and Malaysia. This study aims to analyze the role of the state in guaranteeing legal certainty for the identity rights of children born from unregistered marriages, as well as to identify the similarities and differences in the legal regulations of the two countries. This research is a normative legal study employing statutory, conceptual, and comparative approaches. The primary legal materials in Indonesia include Law Number 1 of 1974 concerning Marriage, Law Number 24 of 2013 concerning Population Administration, the Compilation of Islamic Law, and the Constitutional Court Decision Number 46/PUU-VIII/2010. Meanwhile, the primary legal materials in Malaysia include the Islamic Family Law (Federal Territories) Act 1984 and the Births and Deaths Registration Act 1957. The findings indicate that Indonesia adopts a corrective-progressive approach through the mechanism of isbat nikah (marriage validation) and Constitutional Court Decision Number 46/PUU-VIII/2010, which allows the recognition of civil relations between a child and the biological father based on scientific evidence. In contrast, Malaysia applies a stricter preventive-institutional approach through the Islamic Family Law Act 1984 under the supervision of the Syariah Court. The similarities between the two countries lie in the obligation of marriage registration, the role of religious courts, and their adherence to the Convention on the Rights of the Child (CRC). The principal differences are found in the recognition of civil relations between children and biological fathers, the marriage registration system (centralized versus decentralized), the existence of criminal sanctions, and the orientation of child protection policies. This study recommends the harmonization of regulations based on the principle of the best interests of the child as the foundation for developing responsive Islamic family law policies oriented toward the protection of children’s rights